Intradural Extramedullary Spinal En-Plaque Meningioma With Calcification: A Case Report And Literature Review - siregar, rais; Ibrahim, Sabri (Talenta Universitas Sumatera Utara, 2021)
Abstract Introduction: Intradural extramedullary (IDEM) tumors are benign neoplasms arising in the spinal canal about two-thirds of primary spinal tumors and 15% of tumors affecting the Central Nervous System. Spinal en-plaque meningioma is a type that grows in a sheet-like or collar-like, and incidence in the literature only ranging from 0.1% to 3.1%. Pain is the most clinical symptom, weakness and sensory changes also occur frequently. Magnetic resonance imaging (MRI) is the standard modality for the radiologic diagnosis of meningioma. Case Report: A patient, 35 years old man with a diagnosis of intradural extramedullary spinal meningioma (IDEM) en-plaque with calcification, confirmed by the symptoms, workups such as spinal MRI, and intra-operative findings. The patient was successfully treated surgically with laminectomy and total tumor resection with a posterior approach. Discussion: Spinal en-plaque meningioma is a type that grows in a sheet-like or collar-like manner around the spinal cord can involve dura extensively with significant neurological deficits. Patient was with lower limb weakness, and had a history of back pain radiating to the right limb for the last 1 year. Spinal meningiomas are primarily found in the Intradural Extramedullary, and the tumor diagnosis is typically fairly straight forward based on radiologic findings. Meningiomas are most commonly found in the thoracic region of the spine. In this case from MRI Imaging was revealed a mass in thoracic region of the spine pressing the spinal cord anteriorly. The management of spinal en-plaque meningioma is tumor resection surgery. A retrospective study suggested a significant improvement in neurological deficit post-tumor resection on patients with spinal IDEM tumor. Conclusion: Spinal meningioma is a reasonably frequently found case of a spinal tumor but spinal en-plaque meningiomas are rarely found. MRI scan is the radiological gold standar diagnose spinal en-plaque meningiomas. Patient was successfully treated by total tumor resection using the laminectomy method and tumor resection with a posterior approach without any postoperative complications observed.